MAIN ISSUES OF SUPERVISION OVER THE LEGALITY OF PRE-TRIAL PROCEEDINGS AND CHARGE DEFENSE IN COURT BY THE PROSECUTORIAL GROUP IN THE RA CRIMINAL PROCEDURE - Martirosyan, Arsen (State and Law, 2021)
The Article is devoted to main issues of supervision over the legality of pre-trial proceedings and charge defense in court by the prosecutorial group in the RA Criminal Procedure. Within the framework of the Article, the author discusses the legal grounds for the establishment of the prosecutorial group, as well as issues related to the powers of the members and the head of the prosecutorial group. In the course of the study, the author proposes to subject the grounds for establishing the prosecutorial group to legal regulation, stating that as such can be the complexity of the investigated criminal case, the large volume of the case or the public resonance. At the same time, the author proposes to subject to criminal procedure regulation the powers of the prosecutorial group and the powers of the members of the group, as well as in the case of the establishment of the prosecutorial group, to envisage the mechanisms for introducing the relevant participants of the trial to the superior prosecutor’s instruction regarding the establishment of the group, submitting recusal for each prosecutor of the group as well as for changing the group composition. As a result of the carried out study, the author makes clear offers, which are aimed first at improving the criminal procedure law, solving the problems that occur in practice, also at increasing the efficiency of the prosecutorial supervision and protection of the rights of trial participants.